Efficient Immobilization of Enzymes on Amino Functionalized MIL-125-NH2 Metal Organic Framework - Wang, Zichen; Liu, Yang; Li, Jinhong; Meng, Guoqing; Zhu, Daoyu; Cui, Jiandong; Jia, Shiru (Biotechnology and bioprocess engineering, 2022)
As a series of metal organic framework (MOFs), materials of institute lavoisier frameworks (MILs) are expected to be excellent supports for enzyme immobilization due to their good water-stability and acid tolerance. However, enzyme loading on MIL-125-NH 2 is very low due to small pore size and few amino groups on the surface of the MIL-125-NH 2 . In this work, catalase (CAT) was immobilized on the MIL-125-NH 2 and amino functionalized MIL-125-NH 2 by adsorption (CAT@MIL-125-NH 2 ) and covalent binding (CAT@Amino MIL-125-NH 2 ), respectively. Compared with the CAT@MIL-125-NH 2 and free CAT, the CAT@Amino MIL-125-NH 2 displayed high activity recovery, good pH stability, stability against denaturants, and thermostability. Furthermore, activity recovery of CAT@Amino MIL-125-NH 2 was 56% higher than CAT@MIL-125-NH 2 . The CAT@Amino MIL-125-NH 2 still retained 50% residual activity for 14 days at room temperature, whereas free CAT lost activity after storage for 1 day at the same storage conditions. Furthermore, the CAT@Amino MIL-125-NH 2 maintained 62% of its initial activity after 4 consecutive uses, showing good reusability. The results showed that the amino functionalized MIL-125-NH 2 is an excellent carrier of enzyme immobilization.